Next Generation Sensors and Systems - Mukhopadhyay, Subhas Chandra (Smart Sensors, Measurement and Instrumentation,, 2016)
Written by experts in their area of research, this book has outlined the current status of the fundamentals and analytical concepts, modelling and design issues, technical details and practical applications of different types of sensors and discussed about the trends of next generation of sensors and systems happening in the area of Sensing technology. This book will be useful as a reference book for engineers and scientist especially the post-graduate students find will this book as reference book for their research on wearable sensors, devices and technologies.  .